Catching air : taking the leap with gliding animals - Collard, Sneed B. (How nature works., 2017)
Only a select few animals are able to glide long distances through air, but they include an amazing variety-- even a few species of frogs and snakes. Catching Air takes us around the planet to meet these animals and explore why this gravity-defying talent has evolved in animals, amphibians, and reptiles.